Political graffiti in Prague as a reaction to the Russian invasion of Ukraine in Central Europe - Hána, David; Dresler, Alexandra; Šel, Jan (ERDKUNDE, 2024)
In February 2022, the Russian army attacked Ukraine, which aroused resistance across Europe. The aim of the paper is to analyse spatial concentration and the meaning of associated political graffiti in Prague, Czechia, reflecting reactions to this geopolitical shift. Our approach focuses on the spatial aspect of the socio-semiotic analysis, revealing how urban symbolism shapes graffiti placement, modes, and interpretation. We have mapped it in the areas where we previously had noted a concentration of political graffiti in 2019 and 2020. Thanks to these timelines, we follow the development of political graffiti before and after the invasion and verify if the political symbolic space based on political relations between inhabitants and objects in the urban space influence variations in political graffiti prevalence. We have discovered what opinions resonated in the Czech society and how the meaning of graffiti signs was changing over time, in the space, and among objects of reference.